MENA Regional Economic Update - Freund, Caroline; Ianchovichina, Elena (World Bank, Washington, DC, 2012)
Regional events continue to affect the short-term economic prospects in the Middle East and North Africa (MENA), while major developments in the global economy over the past six months have put the region on a two-track growth path for 2012. These developments include a significant rise in crude oil prices on fears of oil supply disruptions and weak economic activity in the Eurozone. Economic growth of MENA's oil exporting countries will be strong as it rebounds from the average of 3.4 percent in 2011 to 5.4 percent in 2012. In sum, growth in MENA will rebound and approach 4.8 percent in 2012, rising about 2 percentage points relative to growth in 2011. This aggregate outcome however hides a two-track growth forecast. Oil exporters will grow much faster relative to oil importers and relative to 2011, provided oil prices remain strong. Oil importers, especially those recovering after political turbulence, remain in vulnerable positions and will grow at half the pace registered by oil exporters. Risks are multiple and reflect the heterogeneous domestic conditions across MENA, especially in the oil importers and in the global economy.